Temporal relation recognition method based on news event fragments - Ying-jun LI; Hong-li ZHANG; Xing WANG (网络与信息安全学报)
Event fragments as the smallestr unit was defined and a two-stage event fragments temporal relation recognition algorithm was proposed.The first stage is sequential mapping and the second is sequence recognition.The real online data increased accuracy by 4% compared to common classifier and strong rule algorithm.